Exploratory analysis of students’ open-ended responses describing their perception of course inclusivity in an introductory physics course - Vanessa P. Bustamante; Hannah E. Blomgren; Dasha K. Walker; Joshua D. Edwards; Regina F. Frey (Physical Review Physics Education Research, 2024)
In this exploratory study, we examined students’ perceptions of inclusion in a calculus-based, introductory physics 1 course for science and engineering majors. This course, offered at a large R1 institution in the United States, was conducted remotely due to the COVID-19 pandemic. Via a survey given at the end of the semester, students rated their course inclusion and provided open-text explanations for their ratings. On average, students rated the course as moderately inclusive. Using inductive qualitative content analysis, six categories emerged: academic, identity, lack of understanding, nonspecific, other, and remote learning. The top three categories were academic (41%), nonspecific (33%), and remote learning (18%). The remote learning category included phrases containing remote learning, Zoom, or COVID-19, along with a second idea explaining the student’s level of inclusion, leading to remote learning subcategories. These subcategories were similar to the other primary categories and the academic subcategories. Many students cited academic reasons for their inclusivity scores, including course structure, teaching practices, instructor-student interaction, student-student interaction, and overall course environment. Importantly, many of these factors are within the instructor’s influence. Chi-square tests indicated that students perceiving high inclusion emphasized academic factors, while those feeling low inclusion focused on the remote learning aspect of the course. Overall, our findings suggest that instructors can significantly influence students’ perceptions of inclusion through various teaching strategies, interactions between instructors and peers, and a welcoming environment. These insights contribute to the ongoing discussion about creating inclusive classrooms by incorporating student perspectives.